2003
DOI: 10.1381/096089203765887705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Loss on Bone Metabolism: Comparison of Vertical Banded Gastroplasty and Medical Intervention

Abstract: Our data indicate that weight loss causes bone loss. The bone loss is independent of the method of weight reduction. However, the mechanism of the bone loss is not clear. It may be explained partly by reduced estradiol levels in female patients. Because the mechanisms of bone disease after weight loss remain unclear, it is difficult to determine the most effective treatment. It is important to detect osteopenia early, before fractures occur. Measuring BMD appears to be the only reliable method for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 21 publications
7
95
0
6
Order By: Relevance
“…Indeed, according to epidemiological studies, the correlation between BMI and bone mass remains unclear, while another group of studies found that higher BMI was correlated with high bone mass. Furthermore, adipocytes are important sources of estrogen in women for inhibiting bone resorption [45][46][47]. Thus, we found a correlation between estrogen and BMI in the nonosteoporotic group, although the correlation was weak (r=0.21789); these results support that estrogen levels are involved in the complex relationship between BMI and osteoporosis.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, according to epidemiological studies, the correlation between BMI and bone mass remains unclear, while another group of studies found that higher BMI was correlated with high bone mass. Furthermore, adipocytes are important sources of estrogen in women for inhibiting bone resorption [45][46][47]. Thus, we found a correlation between estrogen and BMI in the nonosteoporotic group, although the correlation was weak (r=0.21789); these results support that estrogen levels are involved in the complex relationship between BMI and osteoporosis.…”
Section: Discussionsupporting
confidence: 72%
“…There is a widely held belief that increasing body weight (and thus higher risk of obesity) is associated with lower risk of osteoporosis (Bell 2004;Coates et al 2004;Guney et al 2003;Radak 2004;Wardlaw 1996). However, we previously found that in quantitative genetic analyses that increasing fat mass (thus higher risk to obesity) is actually associated with decreased bone mass (thus higher risk of osteoporosis) when the latter is adjusted for body weight (Zhao et al 2005).…”
Section: Discussionmentioning
confidence: 89%
“…The change in BMD was evident 1 year postsurgery and was associated with the degree of weight reduction [105]. The marked weight loss after long limbbiliopancreatic diversion (BPD-LL) has been associated with decrease in BMD 1 year after surgery [103], RYGB in morbidly obese patients decreases BMC and BMD 1 year postoperatively [106] and, similarly, in a study with follow-up for a year after gastric bypass surgery there was total hip BMD decrease as well as at the lumbar spine [107].…”
Section: Effects Of Bariatric Surgery On Bmdmentioning
confidence: 95%